Selective attention and working memory in young adults born very preterm. - Taylor Mills; Leona Pascoe; Megan Spencer-Smith; Thi-Nhu-Ngoc Nguyen; Peter J Anderson (PLoS ONE)
Introduction Research has consistently reported that individuals born very preterm (VP; < 32 weeks' gestation) are at increased risk for reduced working memory (WM) performance compared with their term born peers. However, performance on working memory tasks are reliant on several cognitive skills, including selective attention, and the underlying mechanism for poorer working memory following VP birth remains unclear. The current study aimed to assess the impact of selective attention on working memory performance in young adults born VP compared with those born at term, using an experimental task (i.e., visuospatial change detection task). Method Participants were 111 young adults born VP (mean age: 20.1 years) and 43 young adults born at term (mean age: 19.9 years). They completed an adapted visuospatial change detection task which assessed working memory maintenance with increasing levels of selective attention demands. Results The VP group demonstrated slightly poorer performance in working memory compared with the term born group when selective attention demands were minimal. The working memory group difference did not increase with the introduction of greater selective attention demands. Conclusion Based on these findings, reductions in working memory performance in those born VP compared with term born controls are unlikely to be explained by selective attention challenges. This study has important clinical implications such that it provides important insights and evidence into the cognitive development of those born VP as they begin to reach adulthood. Further, this research study further the cognitive phenotype of this population, which, in turn, may aid in the development of efficacious cognitive interventions for this high-risk group.